Juridical Overview Regarding the Unenforceability of Court Decisions in Civil Cases That Have Permanent Legal Force (INKRACHT): Tinjauan Yuridis Tentang tidak dapat Dilaksanakannya Putusan Pengadilan dalam Perkara Perdata yang Telah Mempunyai Kekuatan Hukum Tetap (INKRACHT) - Zakariyah, Robitum Maftukh; Riyadh U.B., Ahmad (Universitas Muhammadiyah Sidoarjo, 2020)
The approach is the statute approach, which is to examine the legal rules that apply in Indonesia, relating to the non-enforceability of court decisions in civil cases that already have permanent legal force (Inkracht). Data were collected through primary legal materials which include several laws that refer to civil law and secondary legal materials by digging up information related to the content of the research being studied, and using several books, journals, and previous research. Execution of a decision or what is known as execution is a forced action taken by the Court to a party who has lost to implement a decision that has permanent legal force, this becomes a series of decisions that are included in the end of a civil case process concerning the rights and obligations of a person both in a matter or dispute. From this study it can be concluded that the scope of execution of civil cases in its implementation is divided into two, namely real executions and executions with the payment of a sum of money. However, in carrying out the execution, several legal reasons were found that became obstacles so that the execution could not be carried out, including: the absence of executable assets, the declaratory decision, the object of the execution was in the hands of a third party, the land to be executed was not clearly defined. , changes in the status of land to be owned by the state, and the object of execution is abroad.